Determination of Food Purchase Price in Tourism Objects in The City of Sigli - Benazir Benazir; Zulfa Fuadi (Al Mashaadir : Jurnal Ilmu Syariah, 2022)
This research was conducted to find out the determination of the buying and selling price of food at the Sigli city tourist attraction. Data collection techniques using interviews, observation and documentation. Data analysis in this study will use qualitative data analysis which is constructive, develops and discovers social theories. From the results of this study it was found that there were differences in pricing at the Sigli City tourist attraction. Sellers differentiate prices between one buyer and another by looking at the characteristics of the buyers. If the buyer is from the local area or visitors who frequently visit, the price given is the standard price and if the buyer is considered a new seller, the seller gives a higher price compared to buyers from the local area. According to Islamic law, the practice of buying and selling is carried out by the seller with discriminating between buyers is permissible as long as traders do not take advantage in a way that is prohibited by Islamic law and between sellers and buyers are consensual and mutually willing without any coercion.